Effects of flavonol quercetin on activity of lipid peroxide oxidation in experimental bacterial-immune periodontitis - Demkovych, Andrii (Interv Med Appl Sci, 2018)
The article presents the results of lipid peroxidation activity in blood serum, which were assessed on the base changes in the level of oxidative modification of proteins, TBA-active products, and total amount of nitrogen (II) oxide metabolites (NO(2)(−) + NO(3)(−)). Indices were determined on the 14(th) day of development in experimental periodontitis both without correction, and in condition treatment with a water-soluble flavonol quercetin (corvitin). The treated animals take intramuscular injections of corvitin in a dose 100 mg/kg weight for 7 days. For further testing, blood serum was selected. The results were statistically analyzed using parametric and non-parametric indices. In this investigation, characterized dynamics of changes in the indices of oxidative processes activity were revealed both during the period of formation and the course of periodontitis. In particular, it was found that, for the period of the most expressed inflammatory reaction in the periodontal complex, intensive increase in the level of reactive forms of oxygen. The treatment with flavonol quercetin for 7 days resulted in stabilization of free radical processes and the suppression of the inflammatory reaction.